Westward dharma : Buddhism beyond Asia - Prebish, Charles S.; Baumann, Martin, 1960- (Berkeley : University of California Press, 2002)
The first authoritative volume on the totality of Buddhism in the West, Westward Dharma establishes a comparative and theoretical perspective for considering the amazing variety of Buddhist traditions, schools, centers, and teachers that have developed outside of Asia.
Introduction : Paying Homage to the Buddha in the West / Martin Baumann and Charles S. Prebish -- Part I. Profiling Global Buddhism : a Description of the Landscape -- 1. Who Is a Buddhist? : Night-Stand Buddhists and Other Creatures / Thomas A. Tweed -- 2. The Spectrum of Buddhist Practice in the West / B. Alan Wallace -- 3. Protective Amulets and Awareness Techniques, or How to Make Sense of Buddhism in the West / Martin Baumann -- 4. Studying the Spread and Histories of Buddhism in the West : The Emergence of Western Buddhism as a New Subdiscipline within Buddhist Studies / Charles S. Prebish -- Part II. Diffusion : the Histories of Buddhism in Western Countries -- 5. Buddhism in Europe: Past, Present, Prospects / Martin Baumann -- 6. American Buddhism in the Making / Richard Hughes Seager -- 7. Buddhism in Canada / Bruce Matthews -- 8. The Development of Buddhism in Australia and New Zealand / Michelle Spuler -- 9. Buddhism in South Africa / Michel Clasquin -- 10. Buddhism in Brazil and Its Impact on the Larger Brazilian Society / Frank Usarski -- 11. Buddha in the Promised Land : Outlines of the Buddhist Settlement in Israel /Lionel Obadia -- Part III. Change : Adaptations and Innovations -- 12. Camp Dharma : Japanese-American Buddhist Identity and the Internment Experience of World War II / Duncan Ryuken Williams -- 13. The Translating Temple : Diasporic Buddhism in Florida / Douglas M. Padgett -- 14. Repackaging Zen for the West / David L. McMahan -- 15. Scandals in Emerging Western Buddhism / Sandra Bell -- Part IV. Lifestyle : Being a Buddhist in Western Societies -- 16. The Challenge of Community / Ajahn Tiradhammo -- 17. Buddhist Nuns : Changes and Challenges / Karma Lekshe Tsomo -- 18. Neither Monk nor Nun : Western Buddhists as Full-Time Practitioners / Sylvia Wetzel -- 19. Virtues without Rules : Ethics in the Insight Meditation Movement / Gil Fronsdal -- Part V. Buddhism Facing New Challenges -- 20. The Roar of the Lioness : Women's Dharma in the West / Judith Simmer-Brown -- 21. Engaged Buddhism : Agnosticism, Interdependence, Globalization / Christopher S. Queen -- 22. The Encounter of Buddhism and Psychology / Franz Aubrey Metcalf -- 23. A "Commodius Vicus" Recirculation : Buddhism, Art, and Modernity / Ian Harris.
Includes bibliographical references (pages 383-399) and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Buddhism -- Missions -- History; Buddhism -- History -- 20th century; Globalization -- Religious aspects -- Buddhism; Bouddhisme -- Missions -- Histoire; Bouddhisme -- Histoire -- 20e siècle.; Mondialisation -- Aspect religieux -- Bouddhisme; RELIGION -- Buddhism -- History; RELIGION -- Buddhism -- General; Globalization -- Religious aspects -- Buddhism; Buddhism; Buddhism -- Missions; Boeddhisme; Westerse wereld; Bouddhisme; Mission (Religion); Histoire; 20e siècle.; Occident; 1900 - 1999; asia; australia; buddhism scholars; buddhism; buddhist practices; buddhist studies; buddhist teachings; buddhist traditions; comparative religions; dharma; diaspora; egalitarianism; ethics; europe; global religion; history of buddhism; israel; north america; psychology; religious philosophy; religious scholars; south africa; theoretical approach; theoretical perspective; western buddhists; western philosophy; western thought; western world; zen; History